XÁC ĐỊNH LUẬT PHÂN BỐ XÁC SUẤT CỦA DỮ LIỆU CHẤT LƯỢNG KHÔNG KHÍ ĐƯỢC QUAN TRẮC TẠI HÀ NỘI - Thị Hồng Nhung, Chử; Trung Dũng, Nghiêm (Vietnam Journal of Science and Technology, 2017)
A study to determine the probability distribution of air quality data measured at Hanoi was conducted using the statistical software of SPSS. Data used are hourly average concentrations of air pollutants including SO2, NO2, CO, O3, TSP and PM10 collected from Lang automatic ambient air quality monitoring station, Hanoi for a period of about 8 years, from July 2002 to May 2010. Obtained results show that the Weibull distribution was fitted to the data of hourly average concentrations of these air pollutants. As a result, Probability Density Function (PDF), f(x) and Cumulative Distribution Function (CDF), F(x) for these set of data were determined.